전국 행정기관 담당자 대상 농촌 지역별 노인 맞춤형 식품지원제도를 위한 기반조사 - 육성민(Sung-Min Yook); 김기랑(Kirang Kim); 심재은(Jae Eun Shim); 황지윤(Ji-Yun Hwang) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2019)
본 연구는 노인 대상 지역별 맞춤형 식품지원제도 방안을 제시하기 위한 연구의 일환으로 식품지원제도의 제공자인 전국의 행정기관 담당자들을 대상으로 설문조사를 실시하였다. 전국 행정기관의 노인 및 식품 지원 담당자들을 대상으로 설문지를 배포하고 전체 309부의 설문지를 회수하였으며, 인적사항 및 소속 정보가 미비한 10명을 제외하고 299명의 설문조사 결과를 통계자료로 활용하였다. 전체적인 결과와 함께 행정구역의 규모에 따른 차이를 살펴보기 위해 광역시(n=91), 시 이상의 행정구역 단위(n=118), 군 이하의 행정구역 단위(n=90)의 3군으로 나누어 조사 결과를 비교하였다. 그 결과 담당지역에서 추진하는 노인대상 식품지원서비스와 행정기관 담당자들이 인식하고 있는 담당지역 노인들의 식생활 애로사항은 지역 규모에 따라 차이가 있는 것으로 나타났다. 유･무료 식품지원 후보안의 필요도를 묻는 문항에서는 각 후보안의 평균점수가 모두 보통(5점 중 3점) 이상으로 높았으며, 후보안에 대한 필요도 점수가 전부 높게 나타나 세 지역군 간 유의한 차이가 없었던 것으로 사료된다. 식품지원제도의 활성화를 위해 제도적으로 필요한 요소를 고르는 문항에서는 전담부서 및 인력에 대한 요구도가 모든 지역군에서 가장 높았지만 그 하위의 순위는 지역군마다 다른 결과를 보였다. 이와 같이 본 연구에서는 지역 규모에 따라 식품지원서비스가 다르게 현행되고 있고, 식품지원제도 활성화에 대한 요구도가 다르게 나타날 수 있음을 확인하였다. 이는 향후 식품지원제도가 지역별 특성과 요구도를 반영하여 맞춤형 지원 형태로 보완･발전되어 나아가야 할 필요성을 시사하는 것으로 사료된다. This study conducted a nationwide survey of government officials who are providers of the food assistance system to propose a customized food assistance service for the elderly. The responses from 299 subjects were used for the analysis after excluding 10 subjects without sufficient information. The subjects were compared by dividing them into three groups: metropolitan city (n=91), city unit (n=118), and district unit (n=90), to observe the differences depending on the scale of the administrative district. As a result, the current food assistance services for the elderly were different at three regional groups according to a chi-square test (P<0.001). In addition, the results of the problems of dietary life in elderly (P<0.001), and the requirements for activating the food assistance system (P=0.007) were significantly different in the three groups. The needs for the candidate items of free and paid food assistance service scored high overall. Therefore, in this study, the demand for activating the food assistance system can vary according to the scale of the region, which indicates that a future food assistance system needs to be supplemented and customized to reflect the regional characteristics and needs. KCI Citation Count: 0